Environmental Planning and Forestry - The Canadian Experience - Kumar, Prem (Indian Forester, 1978)
Environmental protection has become a consuming interest in North America in recent years and a number of important publications have focussed interest on it. Currently all projects having an impact on land-use are subjected to predevelopment environmental enquiry. Even the almost inexhaustible forest resources of Canada have felt the burden of agriculture urbanization and intensive forest exploitation of 'c1ean-cutting' system which has left a heavy back-log of unregenerated areas. So, the need of environmental planning has arisen in Canada also. The broad trends and current approaches in environmental planning in forest resources management in Canada are identified under the headings; ecological regionalism, soil, forest inventory, biophysical land classification, Canada land inventory, reforestation and reclamation and land-use planning.